Macrophage Migration Inhibitory Factor is not associated with sarcoidosis susceptibility or severity in whites or blacks - Odio, Camila D.; Miller, Edward J.; Sauler, Maor; Leng, Lin; Piecychna, Marta; Drake, Wonder P.; Bucala , Richard (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine, and increased MIF expression has been associated with the development and severity of multiple granulomatous, autoimmune diseases. However, MIFassociation studies have been discordant in sarcoidosis. Objective: To evaluate associations between macrophage migration inhibitory factor (MIF) promoter polymorphisms and sarcoidosis susceptibility and severity. Methods: Three hundred and fifty one patients with sarcoidosis were recruited through the Genomic Research in Alpha-1 Antitrypsin Deficiency and Sarcoidosis (GRADS) study. Genomic DNA was isolated from serum, and the MIF -173G/C SNP [rs755622] and MIF -794 CATT5–8microsatellite repeat [rs5844572] were genotyped. Allelic frequencies were compared between cases and healthy controls and associations between MIF alleles and sarcoidosis severity were assessed. Results: The frequencies of the high expression -173C SNP and the low expression -794 CATT5containing genotypes in white and black sarcoidosis patients were the same as those of healthy controls. High expression MIF alleles were not associated with sarcoidosis severity. Associations between MIF alleles and extrapulmonary sarcoidosis phenotypes were limited by small sample sizes. Conclusions: High expression MIF genotypes were not associated with the susceptibility to or severity of pulmonary sarcoidosis in a large North American cohort.